Konsep Alam Coffee Shop Pikaco Dan Watu Sangan Di Pemalang Sebagai Strategi Komunikasi Pemasaran Dalam Meningkatkan Brand Image - Nanda Tyas Prayoga; Ike Desi Florina; Sarwo Edy (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
The natural concept of Pikako Coffee Shop and Watu Sangan Coffee Shop is based on natural conditions, without using luxurious buildings. Both carry the Dupont House concept, the seating is made of wood, and although it cannot be called luxurious, the views and surroundings are comparable to an urban cafe. The nature of the Komal River has its own attraction for tourists, especially those from outside the city. This research examines how the natural concept used in two cafes in Pemalang Regency, Pikaco and Watu Sangan, is used as a marketing communication strategy to improve brand image by using interviews as a data collection technique. The results of this research are the natural concept used in Pikako and Watu Sangan coffee shops, product supporting theory, price, location, promotion, and brand image, three factors to increase the popularity of Brand Association Benefits. Brand Association Strength Brand Association Uniqueness Using descriptive qualitative research methods and interview techniques, obtain data to improve brand image.